Utilizing Flat Coil-Based Vibration Sensor on A Bamboo Drum as Disaster Preparedness Media For Students - Islahudin Islahudin; Haifaturrahmah Haifaturrahmah; Muhammad Nizaar; Soeharto Soeharto (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
People's awareness of earthquakes is very deficient, and their earthquake mitigation is also relatively scant. The research objectives are: 1) Designing a flat coil-based vibration sensor on a Security Pos Drums as a Disaster preparedness media for Muhammadiyah Elementary School students; 2) Analyzing how high the level of disaster preparedness for Muhammadiyah Elementary School students through a flat coil-based vibration sensor on the Security Post Drums. This study uses two methods, i.e., 1) The experimental method was used to design the flat coil-based vibration sensor installed on the Security Post Drums. The vibration frequency measured by the flat coil sensor is the low frequency. The Security Post Drums work by striking it once or more, and then the vibration propagates to the sensor so the siren will blare; and 2) Qualitative and quantitative method used to measure students' preparedness in Muhammadiyah Elementary School. The samples applied are 26 students taken by random sampling method. The data on students' preparedness was collected using a questionnaire instrument. The research variable of the preparedness consisted of 5 aspects, i.e., 1) knowledge on types of disasters; 2) steps taken at the beginning of a disaster; 3) steps undertaken right after the disaster occurred; 4) materials need to prepared when disaster struck, and 5) preparedness in dealing disaster. The assessment was carried out using the Likert scale. The results of this research are 1) the disaster preparedness media for Aisyiyah Elementary School students has been designed in a flat coil-based sensor integrated with security post drums); 2) the level of disaster preparedness for Aisyiyah Elementary School students increased. This improvement was indicated that the posttest score (ranges from 60 until 68.18) was more significant than the pretest score (ranges from 49 until 58) on the overall five aspects.